TEKNIK TRADISIONAL UKIR LOGAM DI DESA TUMANG CEPOGO BOYOLALI - Aan Sudarwanto; Kuntadi Wasi Darmojo (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
ABSTRACT The article entitled Teknik Tradisional Ukir Logam Di Desa Tumang Cepogo Boyolali (Metal Carving Traditional Technique) in TumangCepogoBoyolali Village is one of the results of research that was applied to community service activities (PPM) with the title PPPE Kriya Logam Pada Sentra Kerajinan Tembaga, Kuningan dan Aluminium di Desa Tumang Cepogo Kabupaten Boyolali, Jawa Tengah (PPPE KriyaLogam at the Copper, Brass and Aluminum Craft Centers in Tumang Village, Cepogo, Boyolali Regency , Central Java). The purpose of the study was to identify and find out more about the technicality of metal crafts, especially the carving techniques found in TumangCepogo village, Boyolali, Central Java as data for engineering development. Metal crafts in Tumang village are hereditary cultural heritages that produce a lot of household appliances such as dandang, wajan, kwali, kendil, and others. Along with the time progress, it experiences developments with a touch of aesthetic creativity thatbecomes high-quality handicraft art items. the technique used in this develop-ment is metal carving techniques. Based on this, research on metal carving techniques has become important in relation to product development and the quality of high-quality crafts. The method used in this study belongs to the qualitative category. Some approaches are used in analyzing data, including interactive analysis. It is a flowing relationship of three main components, namely data reduction, data presentation and drawing conclu-sion whose activities are carried out interactively, thus carried out repeatedly so that it formsa cycle.